Oh! Oh! The giant has awaken! Brazil, June 2013: concepts and metaphors of the street marches - Almeida, Ariadne Domingues (2016)
Results are presented featuring a study on the process of the conceptualization of the 2013 street manifestations in Brazil and their social agents. Cognitive Linguistics, based on Lakoff and Johnson (1980), Kövecses (2009), Grady (1997) and others, foregrounds the theoretical-methodological basis of current research. Corpus comprised postings on Facebook retrieved in June 2013. Qualitative data analysis showed that the street manifestations may be conceptualized as war through the metaphor’s mechanism.